Iron cytochrome C nanohybrids - Supramolecular electron transfer to an electron accepting fullerene - Guldi, Dirk Michael; Zilbermann, Israel; Hatzimarinaki, Maria; Hirsch, Andreas (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2006)
For the first time, intracomplex electron transfer reactions were tested in cytochrome c based nanohybrids (i.e., Fe(II)CytC and Fe(III)CytC), to which polyanionic C derivatives were electrostatically associated. Successful radical ion pair formation, namely, oxidized FeCytC and reduced C, was detected when divalent Fe(II)CytC is used. The so formed Fe(III)CytC · C lives for 2.4 ± 0.5 μs. © by Oldenbourg Wissenschaftsverlag.